The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1073/pnas.86.18.6893
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K-dependent carboxylase: affinity purification from bovine liver by using a synthetic propeptide containing the gamma-carboxylation recognition site.

Abstract: The vitamin K-dependent carboxylase catalyzes the posttranslational modification of specific glutamic acid residues to form rcarboxygutam acid residues within the vitamin K-dependent proteins. This enzyme renizes the 'y-carboxylation recognition site on the propeptide of the precursor forms of the vitamin K-dependent blood cogulation proteins. To purify this enzyme to homogeneity, the carboxylase from bovine liver microsomes was solubilized with 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (CHAPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…The entire purification can be accomplished in 4 days. It is difficult to compare different purification schemes but, by comparing final specific activities, it appears that our puri- fication results in a carboxylase preparation that 185-fold higher specific activity than the best previously published method (11). From 14CO2 incorporation into the pentapeptide FLEEL, we estimate the specific activity of our carboxylase prepared by Affi-FIXQ/S chromatography eluted by method II (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire purification can be accomplished in 4 days. It is difficult to compare different purification schemes but, by comparing final specific activities, it appears that our puri- fication results in a carboxylase preparation that 185-fold higher specific activity than the best previously published method (11). From 14CO2 incorporation into the pentapeptide FLEEL, we estimate the specific activity of our carboxylase prepared by Affi-FIXQ/S chromatography eluted by method II (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Harbeck et al (10) extended this method by eluting the carboxylase from a prothrombin antibody column with a synthetic propeptide achieving a 500-fold purification and a final specific activity of6.6 x 106 cpm per mg per hr. Hubbard et al (11) reported the purification of the carboxylase to homogeneity using a synthetic propeptide sequence as an affinity ligand. However, the reported final specific activity of 1.3 x 107 cpm per mg per hr was still not significantly different than that reported by Girardot (8).…”
mentioning
confidence: 99%
“…OC and mutant OC (the 3 glutamic acid residues, Glu [positions], had been mutated to aspartic acid residues [Asp]) constructs were provided by Caren Gundberg (33). pLIVE expression vector, a vector driven by a liver-specific promoter composed of the minimal mouse albumin promoter and the mouse α-fetoprotein enhancer was purchased from Mirus Bio.…”
Section: Methodsmentioning
confidence: 99%
“…This method of controlling the carboxylation status of osteo calcin has been previously used to inactivate vitamin K-dependent clotting factors (33). Furthermore, for validation purposes (see below), we cloned green fluorescent protein (gfp) into the pLIVE vector.…”
Section: Figurementioning
confidence: 99%
“…Anti-carboxylase-(86-99) antibodies were affinitypurified as described (13 Bovine Liver Carboxylase Purification. Isolation of microsomes from fresh bovine liver was performed as described (10). Carboxylase was solubilized with CHAPS and concentrated by precipitation with ammonium sulfate.…”
mentioning
confidence: 99%